The Role of Parents in Shaping a Child's Personality in Islam - Adililham, Adililham (Cita konsultindo, 2023)
The Role of Parents in Shaping a Child's Personality specially in Islam is crucial in the development and growth of children, considering that the future of the nation lies in the hands of today's children, who face various challenging obstacles. The decline in morals, virtues, and etiquette in today's society poses a challenge for parents to transmit understanding and practice moral and ethical values to their children. A child's personality is formed through the interaction, influence, and education provided by parents throughout their growth. The purpose of this research is to explain the role played by parents in shaping a child's personality. This study is a literature review conducted using qualitative research methods and a descriptive approach. Data analysis of the subject matter is carried out using an inductive approach, with data sourced from books, journals, and scientific writings related to the examined subject. The results of the research indicate that parents play a significant role in shaping a child's personality. They serve as role models, provide guidance and direction, instill moral and ethical values, and offer emotional support to their children. Furthermore, effective communication and positive interaction between parents and children also play an important role in shaping a child's personality. The role of parents in shaping a child's personality cannot be ignored. Through interaction, influence, and education provided by parents, children can develop a healthy, responsible personality with positive values. Therefore, it is crucial for parents to be aware of their role and actively engage in shaping their children's personality development.